GAYA HIDUP, MANAJEMEN KEUANGAN, STRATEGI KOPING, DAN KESEJAHTERAAN KELUARGA NELAYAN - Johan, Irni Rahmayani; Muflikhati, Istiqlaliyah; Mukhti, Dewi Sekar (Jurnal Ilmu Keluarga dan Konsumen, 2013)
The aim of this research was to analyze the influence of family characteristic, lifestyle, financial management, and coping strategies toward the fisherman families well-being (objective and subjective). The study involved 88 fisherman families which having school children and were chosen purposively. Data was collected by interview and analyzed by descriptive, hierarchical cluster analysis, multiple linear regression analysis, and logistic regression analysis. The research results showed that the lifestyle of fisherman families were family oriented. Financial management was categorized as medium. When they were having the decrease of income, they tend to do cutting back as coping strategies rather than generating income. Most of fisherman families are classified as nonpoor by objective indicator. The objective well-being was influenced by the family size and family income per capita per month. Meanwhile, the subjective well-being of fisherman families were categorized as medium. The subjective well-being was influenced by wifes’ age and productive oriented lifestyle.